Nursing practices associated with suicide prevention dynamics: An experience report (Research, Society and Development, 2021)
Suicidal behavior refers to a series of suicide-related phenomena, the most relevant of which are suicide itself (death) and attempted suicide. Therefore, it is up to nursing professionals to apply behaviors based on scientific knowledge in mental health, to prevent the realization of such an act. With this study, the objective was to report the experience in a health education group based on the dynamic activity alluding to the yellow September. This is a descriptive study with a qualitative approach in the experience reporting modality, in which participant observation by nursing students during the health education group was applied. In dynamic activities, users received balloons and the mission to keep the balloon “safe”, however, they were motivated to move the body and the balloon. Then, questions were asked with questions, which they needed to solve in twenty seconds, if they couldn't, they should pop the balloon. Subsequently, users were told that the balloon represented life, generating a reflection on problems, resolutions and suicide, each of whom must express on paper how they felt from the reflection exposed. Throughout the dynamic activity, users participated actively, being instructed to ask for or seek help when they present difficulties in resolving crises, and to avoid using psychoactive substances as adaptive strategies to face suffering.